Cântico dos Cânticos e o amor humano: um estudo a partir da psicologia junguiana - Silva, Reginaldo de Abreu Araujo da (2008)
The Song of Songs is a book of the Bible whose subject is human love. The book has been, during two millenniums, interpreted as allegory, by Jewish and Christians. The Jewish interpreted the beloved man as a figure of God and the beloved woman as a figure of Israel. Christians interpreted man like Christ and woman like the Church, the human soul or the Virgin Mary. It was at the end of 19th century that appeared the literal interpretations which developed with much force in the 20th century. Literal interpretations describe the beloved man and the beloved woman like two human beings who become acquainted to affection, love and sexual relationship and the book is accepted as a canonical text in the Holy Bible. One of the possibilities of literal interpretation of Song of Songs is the psychological interpretation, starting with symbols and psychic process that are lived by the beloved man and the beloved woman. The Jungian psychology offers some elements to interpret the love relationship as coniunctio and to do an analysis of the archetypes from human psyche, for example: anima, animus, persona, shadow. The love relationship bases the intimate relation and makes possible the grades of psychic process that, according to Jungian psychology, is a process of individuation. This process leads the Self, which is more important archetype of psyche and so, the human being may be happy and be self realized. In the Song of Songs we may perceive the individuation process and the beloved man and the beloved woman being self realized in the love affair and in the Hebrew conception love is like a flame of Yahweh, the God of Israel, and like a strong love which is strong as death. The process initializes but does not end, because it is the property of human psyche in a continuous research of individuation and of self realization